Fashion marketing and communication : theory and practice across the fashion industry - Mitterfellner, Olga, 1978- (Routledge, Taylor & Francis Group, 2020)
"Some of the usual obstacles to modern teachings of marketing are ethnocentricity, the limitation of creative thought by conformity to existing theories, lack of questioning of ethics, and a disconnection from historic events or sociological discourse. This book, in contrast, draws together interdisciplinary approaches from marketing, branding, promotion and critical media studies as tools for understanding the way in which fashion works today, and re-evaluates what makes certain fashion marketing tactics fashionable. Offering a combination of theory and practice, Fashion Marketing and Communication is full of international case studies, practice-based examples, and interviews with scholars and practitioners in the fashion and communications industry. Covering subjects including the history of consumerism, fashion marketing, the creative direction of the fashion brand and the use of bloggers and celebrities as marketing tools, this book delineates the opportunities and challenges facing the future of fashion media in the 21st century. Examining the last 100 years of marketing and communications, current theory and practice, as well as questions on the ethics of the fashion industry, this broad-ranging and critical text is perfect for undergraduate and postgraduate students of fashion marketing, branding and communication"- Resumé vydavatel